The Effect of Trust and Service Quality Toward Patient Satisfaction with Customer Value as Intervening Variable - Laura, Netty (Bina Nusantara University, 2016)
The research was conducted at Laboratory Installation RSPI of Prof. Dr. Sulianti Saroso (RSPI-SS). Unit of analysis was patients of Medical Check Up in Laboratory Installation of RSPI-SS which is located in Sunter, North Jakarta. The samples of this research were 93 patients from 121 populations; the research method was purposive sampling technique. The instrument of statistic analysis was through PLS 3.0 which was used to test the hypothesis. The research finds seven hypotheses as the results. They are variable of trust which affects customer satisfaction positively but does not significantly affect to customer satisfaction, variable of trust which affects customer satisfaction negatively but significantly affects the customer value, variable of service quality which affects to customer satisfaction positively and significantly, variable of service quality which affected to customer value positively and significantly, variable of customer value which affects positively and significantly to customer satisfaction, intervention of customer value on the trust to customer satisfaction which affects negatively and significantly, and intervention of customer value on service quality to customer satisfaction which affects positively but not significantly.